Out-of-pocket expenditure and catastrophic health expenditure in patients of leprosy at a tertiary care center in India - Kavita Kavita; Sukhdeep Singh; Kittu Malhi; Manisha Upreti; Sushma Saini; Arushi Ghai; Ritin Mohindra; Tarun Narang; Sunil Dogra (Transactions of The Royal Society of Tropical Medicine and Hygiene, 2026)
Abstract Objectives Leprosy continues to impose a significant clinical and socioeconomic burden. Despite free multidrug therapy, patients incur substantial out-of-pocket expenditure (OOPE), leading to catastrophic health expenditure (CHE). Evidence on the economic burden of leprosy in India remains limited. Methods A pilot prospective observational study was conducted at a tertiary care center in North India, enrolling 56 patients with leprosy. Data on sociodemographic characteristics, direct and indirect healthcare costs, and income were collected. Results The study population had a median age of 30 years, with 73% males, and 68% from rural areas. Multibacillary disease predominated (93%), with complications in 73.2% and a median diagnostic delay of 24 months. Median monthly household income was Indian Rupees (₹)12 000, while median OOPE was ₹1625, largely driven by medicines and travel. CHE was observed in 55.4% of patients. OOPE was significantly higher in multibacillary cases compared with paucibacillary disease (P = .04). A considerable proportion of patients resorted to borrowing money, indicating financial distress. Conclusion Leprosy imposes a substantial financial burden, with more than one-half of patients experiencing CHE. Strengthening early diagnosis, decentralizing care, and improving financial protection mechanisms are essential to mitigate economic hardship.